Experimental analysis of time dependent phenomena and temperature effects on macro-synthetic fibre reinforced concretes in different loading conditions. (4th April 2022) - Del Prete, C.; Buratti, N.; Mazzotti, C.
Highlights: Long-term characterization of Fiber Reinforced Concretes mechanical behaviour is not fully standardized yet. Multiple mechanisms interact when structural elements are subjected to sustained flexural load: compression of concrete, tension of fibers and fiber-concrete interaction. The dispersion of the fibers on the specimen cross section determines the mechanical behaviour. The comparison of the deformations in terms of creep coefficient allows to quantify the predominant mechanism in the flexural state. Creep tests in different loading conditions characterize the mechanical behaviour in service of fiber reinforced concretes. Abstract: Fibre reinforced concretes (FRCs) are composite materials now largely adopted in structural applications given their mechanical properties in terms of the residual tensile strength, almost absent for plain concrete. The short-term mechanical behaviour of these material has been deeply studied, while their time-dependent deformations have received less attention from the scientific community. The present paper presents the experimental characterization of the creep deformations of a concrete reinforced with polypropylene fibers by means of different types of tests, together with an analysis of the temperature effect. Innovative test set-ups are used to this aim. The paper presents the results of shrinkage, compression creep, uniaxial tension and flexural creep tests and discusses the contribution of the different components of the FRC to the composite creep behavior.